Electromagnetic Analysis and Comparative Study of Surface-Mounted and Consequent Pole Axial Flux Permanent Magnet Machines - Rajesh Kumar; Dae Yong Um; Lars Sjoberg; Tushar Batra; Glynn Atkinson (IEEE Access, 2024)
This research presents a comparative analysis of single-sided surface-mounted axial flux permanent magnet (SMAFPM) and consequent-pole axial flux permanent magnet (CPAFPM) machines by evaluating various key electromagnetic parameters. A straightforward replacement of permanent magnets (PMs) with soft magnetic composites (SMCs) is proposed for a conversion of surface-mounted (SM) topology to consequent pole (CP) topology, which maximizes manufacturing ease while sharing the same components. Detailed three-dimensional (3D) finite element analysis (FEA) is performed to assess parameters such as back-EMF, flux-linkage, inductance, torque, and losses. The investigation highlights that despite utilizing 50% less rare-earth permanent magnet (PM) material, the CPAFPM machine produces only 30% less rated torque compared to the SMAFPM machine. However, the CPAFPM machine suffers from reduced magnetic loading and higher armature reaction, leading to 36% lower torque density and reduced efficiency at low speeds and heavy loads. Prototypes of both machines were fabricated, and experimental validation showed a good correlation with the simulation studies. The findings provide insight into the simple conversion to the CPAFPM machine as a viable option for high-speed drives requiring fewer rare-earth PM materials.